2019
DOI: 10.1039/c9ra01143a
|View full text |Cite
|
Sign up to set email alerts
|

Cu@Co-MOFs as a novel catalyst of peroxymonosulfate for the efficient removal of methylene blue

Abstract: In this study, for the first time, we describe the single step synthesis of a Cu particle-doped cobalt-based metal–organic framework (Cu@Co-MOF) using a hydrothermal method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…12 By considering the toxic effects of homogeneous transition metal ions (e.g., Co 2+ , Fe 3+ , Cu 2+ ), there are numerous interests to develop highperformance heterogeneous catalysts to active PMS/PDS. 13,14 Literature review indicates that metal-based heterogeneous catalysts, including zero-valence metal, 15 metal oxides, 16 zeolite, 17 and metal−organic frameworks, 18 dominate the related research in the past few years. It is unfortunate that no matter how these metal-based catalysts are elaborately designed, the leaching of metal ions cannot be suppressed completely because electron transfer during the activation process will facilitate the dissolution of metal active sites.…”
Section: •−mentioning
confidence: 99%
See 1 more Smart Citation
“…12 By considering the toxic effects of homogeneous transition metal ions (e.g., Co 2+ , Fe 3+ , Cu 2+ ), there are numerous interests to develop highperformance heterogeneous catalysts to active PMS/PDS. 13,14 Literature review indicates that metal-based heterogeneous catalysts, including zero-valence metal, 15 metal oxides, 16 zeolite, 17 and metal−organic frameworks, 18 dominate the related research in the past few years. It is unfortunate that no matter how these metal-based catalysts are elaborately designed, the leaching of metal ions cannot be suppressed completely because electron transfer during the activation process will facilitate the dissolution of metal active sites.…”
Section: •−mentioning
confidence: 99%
“…Sulfate radical (SO 4 •– ) has been considered as a kind of promising active species in advanced oxidation technologies (AOTs) for wastewater remediation in the past decades. Compared with the conventional hydroxyl radical ( • OH), SO 4 •– has established its advantages of higher oxidation potential, longer lifespan, and wider pH range for powerful mineralization as well as dispensable sludge disposal. The generation of SO 4 •– is usually realized by peroxymonosulfate (PMS) or peroxydisulfate (PDS) activation. , Although some physical techniques, such as ultrasound, UV irradiation, and heating, may work for the activation process, the high-energy input restrains their extensive application to some extent. Anipsitakis and Dionysiou demonstrated that catalytic activation was a highly effective way to produce SO 4 •– without the limitation of the operation conditions . By considering the toxic effects of homogeneous transition metal ions (e.g., Co 2+ , Fe 3+ , Cu 2+ ), there are numerous interests to develop high-performance heterogeneous catalysts to active PMS/PDS. , Literature review indicates that metal-based heterogeneous catalysts, including zero-valence metal, metal oxides, zeolite, and metal–organic frameworks, dominate the related research in the past few years. It is unfortunate that no matter how these metal-based catalysts are elaborately designed, the leaching of metal ions cannot be suppressed completely because electron transfer during the activation process will facilitate the dissolution of metal active sites …”
Section: Introductionmentioning
confidence: 99%
“…1 Not only do they cause damage to the ecosystem but they are also harmful to human beings. 2 Methylene blue (MB) is one of the most commonly used cationic dyes. 3 It could cause many harmful effects on human beings, such as nausea, mental confusion, jaundice, quadriplegia and tissue necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Removing pollutants from wastewater is one of the most effective ways to access clean water [ 2 ]. Organic dyes, which are widely used in printing, papermaking, textile, plastics, leather tanning, cosmetics, and other industries, are among the most significant forms of industrial wastewater in China [ 3 , 4 , 5 ]. Although the presence of organic dyes is not highly toxic in the environment, they still cause many adverse effects on organisms, such as mutagenesis, carcinogenicity, respiratory toxicity, and teratogenicity [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%